2020
DOI: 10.1136/svn-2020-000347
|View full text |Cite
|
Sign up to set email alerts
|

Advances in endovascular aneurysm management: flow modulation techniques with braided mesh devices

Abstract: Flow diverters and flow disruption technology, alongside nuanced endovascular techniques, have ushered in a new era of treating cerebral aneurysms. Here, we provide an overview of the latest flow modulation devices and highlight their clinical applications and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 105 publications
0
13
0
2
Order By: Relevance
“…Braided devices such as Flow-Diverters (FDs, see Fig. 1b) are an excellent option in particular to tackle complex aneurysmal geometries (wide neck or small dome-to-neck ratio) [6] . As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Braided devices such as Flow-Diverters (FDs, see Fig. 1b) are an excellent option in particular to tackle complex aneurysmal geometries (wide neck or small dome-to-neck ratio) [6] . As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 1c, these devices consist of a very dense weave of thin metallic wires with diameters around 30 µm, generally made of Nitinol or Cobalt-Chromium [6] . They redirect blood into the parent artery and impede the flow at the aneurysm neck, thus reducing intra-aneurysmal velocities.…”
Section: Introductionmentioning
confidence: 99%
“…Coil embolization is an effective treatment procedure with a low complication rate of 3.7% but a high rate of incomplete obliteration (up to more than 40% of the cases [38,41]). Implantation of flow diverting stents yield an occlusion rate between 62.8 and 93.9% at 1 year with a mortality rate up to 5.5% [42]. Microsurgical clipping results in very low aneurysm recurrences (1.5%) of completely clipped aneurysms, however in much more frequent recurrences in cases with incomplete clipping [39,40,43].…”
Section: Clinical Management Of Iamentioning
confidence: 97%
“…The most common neurological manifestations include headache and dizziness, followed by delirium, that often is the first manifestation of COVID-19 in older adults [ 3 , 4 ]. However, similar to other viruses, some literature has reported the presence of cerebrovascular events (such as stroke), Guillain–Barre syndrome, acute transverse myelitis, and acute encephalitis in people affected by COVID-19 [ 5 ]. Of importance, it is has been reported that neurological manifestations may precede the typical features of COVID-19 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%